Lenin’s Language in the Assessment of Russian Formalists. Rhetorical Analysis - Khazagerov, Georgy (Literatūra, 2024)
The article is dedicated to Lenin’s language. The interpretation of the language of Lenin by representatives of the Russian formal school is examined. The material of the article is the publications of the six best representatives of this school in 1924. The article raises the question of whether Lenin’s language is really close to the language of the Russian avant-garde, as the authors of the publications insist. Today, this question remains relevant in the light of the theory of two cultures within the Soviet one – revolutionary and protective – as well as in the light of the rapprochement of formalists with post-Marxist criticism. The provisions of the formalists are considered in the article from the perspective of rhetorical discourse analysis. Four theses about Lenin’s language put forward by the formalists are consistently questioned. The idea of the special clarity of Lenin’s language, which Soviet linguistics insisted on, is also challenged.
Keywords: Lenin’s language; discourse; style; manipulation